Synthesis of tacrine analogues derived from n-aryl-5-amino-4-cyanopyrazoles - Rodrigues, Lígia M. (2008)
Synthesis of eleven tacrine analogues derived from N-aryl-5-amino-4-cyanopyrazoles, by a Friedländer type reaction, is described. Their structures were confirmed by 1H and 13C NMR spectroscopy, elemental analysis and/or mass spectrometry.